Comprehensive update on the monkeypox outbreak - Karim, Asad Mustafa; Kwon, Jeong Eun; Karim, Mujahid Aizaz; Iftikhar, Haseeb; Yasir, Muhammad; Ullah, Irfan; Kang, Se Chan (Frontiers in Microbiology, 2022)
Monkeypox (MPX) was first reported in 1970 in humans and outbreaks were restricted and highly localised to endemic regions of western and central Africa. However, after the first reported case in the UK in early May, 2022, the pattern of epidemic spreading in the geographical regions was much larger compared to past, posing a risk MPX might become entrenched beyond endemic areas. This virus is less transmissible than SARS-CoV-2, as it transmitted mainly through personal, close, often skin-to-skin contact with infectious MPX rash, body fluids, or scabs from an individual with MPX. Infections usually present with chills, fever, fatigue, muscle aches, headache, sore throat, skin lesions, and lymphadenopathy. Currently, there are no antivirals approved for MPX. However, an antiviral drug called “tecovirimat”, approved for the treatment of smallpox, has been made accessible to treat MPX. Moreover, to prevent MPX, there are two vaccines available which are approved by FDA: Bavarian Nordic JYNNEOS, and ACAM2000 vaccine. Contact tracing is absent in case of MPX outbreak and there is lack of information from the data systems in rapid manner. Additionally, test capacity needs to be increased. Like SARS-CoV-2, global MPX outbreak demand for vaccines far exceeds availability.